Two cemeteries at Takhtidziri (Georgia) : late Achaemenid-early Hellenistic and late Hellenistic-early Roman - Gagoshidze, I͡U. M.; Vickers, Michael J.,; Kacharava, D. D.; Gagoshidze, David, (Archaeopress Archaeology, 2022)
This work publishes excavations at two cemeteries located near to the village of Takhtidziri in Shida Kartli, the central region of Georgia. The grave goods recovered are diverse and suggest that the kingdom of Kartli (Caucasian Iberia) was involved in international trade and economic relations in the late Hellenistic and Early Roman period.